Hugh McCulloch papers - McCulloch, Hugh, 1808-1895.
Primarily correspondence with some speeches, reports, and other material relating to McCulloch's career as a banker and financier, as U.S. comptroller of the currency (1863-1865), and as U.S. secretary of the treasury (1865-1869 and 1884-1885). Subjects include enfranchisement of African Americans, currency, national debt, finance, politics, Reconstruction, and tariff. Correspondents include Edward Atkinson, James Gillespie Blaine, George S. Boutwell, William E. Chandler, Salmon P. Chase, Schuyler Colfax, Samuel Sullivan Cox, William Pitt Fessenden, John Murray Forbes, Morris Ketchum, Joseph Medill, John Sherman, John Aikman Stewart, Charles Sumner, and Robert C. Winthrop.
U.S. secretary of the treasury, banker, and financier.
Collection material in English.
Keywords: Atkinson, Edward, -- 1827-1905 -- Correspondence; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Boutwell, George S. -- 1818-1905 -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Cox, Samuel Sullivan, -- 1824-1889 -- Correspondence; Fessenden, William Pitt, -- 1806-1869 -- Correspondence; Forbes, John Murray, -- 1813-1898 -- Correspondence; Ketchum, Morris, -- active 1864 -- Correspondence; Medill, Joseph, -- 1823-1899 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Stewart, John Aikman, -- 1822-1926 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Winthrop, Robert C. -- 1809-1894 -- Correspondence; United States. -- Department of the Treasury. -- Office of the Secretary; United States. -- Office of the Comptroller of the Currency; African Americans -- Suffrage; Banks and banking -- United States; Debts, Public -- United States; Finance -- United States; Finance, Public -- United States; Money -- United States; Reconstruction (U.S. history, 1865-1877); Tariff -- United States; United States -- Politics and government -- 19th century; Bankers; Cabinet officers; Financiers